Ergonomic Implementation Smile Applications Improve Employee Performance and BPJS Ketenagakerjaan Service Speed in Bali - Lestari, Ni Putu Nila; Adiatmika, I Putu Gede; Sudarma, Made (Program Studi Magister Ergonomi Fisiologi Kerja Pascasarjana Universitas Udayana Denpasar Bekerjasama dengan Perhimpunan Ergonomi Indonesia (PEI), 2021)
The type of service that BPJS Ketenagakerjaan participants want when accessing work accident services is that good employee performance has increased the speed of service at work. For this reason, an intervention was implemented in the form of implementing ergonomics in the SMILE application to improve service speed, improve employee performance and reduce eye fatigue rates for Bali BPJS Ketenagakerjaan employees. This research was an experimental research with treatment by subject design, which involved 16 research samples. There were two periods, namely Period I work process without intervention and Period II work process with interventions in the form of implementing ergonomics in the SMILE application through to IEMAS application. The service speeds were measured with a stopwatch and employee performances were measured by performance questionnaires and eye fatigue. An eye fatigue questionnaire measured the data. Data analysis that uses a T-paired test with a value of ? 0.05 is for normally distributed data and Wilcoxon test is for data that is not normally distributed. Data obtained from the study results showed differences in employee performance with decreased eye fatigue and increased work comfort and service speed (p<0.05). Improved employee performance indicated the results of research in which there was a decrease in eye fatigue in employees by 8.77%, an increase in work comfort by 12.05% and service speed by 89.1%. It can be concluded that the implementation of the SMILE application reduces the rate of eye fatigue and increases the comfort of the work of employees, resulting in the speed of employee services to participants BPJS Ketenagakerjaan in Bali